Desenvolvimento de sistema de monitoramento IoT para rios urbanos de fácil implantação e baixo custo - Silva Menezes, Luana Maria da (Universidade Federal de São Carlos, 2020)
The phenomenon of urbanization in Brazil has triggered - not only alone, but in conjunction with other factors - the housing occupation of areas of riverside floodplain in a disorderly manner. Such occupations, however, pose great risks to their residents and passersby due to the possibility of unexpected floods that can generate human and economic losses. In this context, several actions can be taken to mitigate this problem and new ways of reducing the damage caused by this type of natural disaster intensified by human activity have been sought in technology. One of them, which does not involve structural changes, would be the adoption of river monitoring systems with remote sensing, in real time, of the water level and issuing alerts to the local population from the occurrence of possible floods. However, currently, most expensive, proprietary solutions for this problem are available on the market, and there are few Brazilian solutions. Of these, the TerraMA 2 tool stands out, which is open source and developed by researchers, but its manipulation and implementation is complex, and consequently of high cost due to the need for specialized study. Thus, there is a need to develop a system that can meet these specifications and that is low cost, easy to implement and use, aiming primarily to meet the urgent demand for responses to reduce the damage caused by urban floods. In this work, the creation of a monitoring station prototype with sensors controlled by the Arduino microcontroller was initiated. The data is sent in real time by MQTT and stored in a relational database. Measurement reliability tests were performed on the sensors and a solution was proposed for the problems encountered. The reliability of sending information from stations to the server in the cloud through mobile networks was also tested. It is expected that the establishment and other tests of the system will take place in the central region of the São Carlos unicity (SP), a region with an important history of flooding.
Development of a low cost IoT monitoring system for urban rivers that are easy to implement
Keywords: MQTT; Internet das Coisas; Sistemas Embarcados; Rios; Enchentes; monitoramento; Arduino; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO